Contact-dependent depletion of hydrogen peroxide by catalase is a novel mechanism of myeloid-derived suppressor cell induction operating in human hepatic stellate cells - Resheq, Yazid J.; Li, Ka-Kit; Ward, Stephen T.; Wilhelm, Annika; Garg, Abhilok; Curbishley, Stuart M.; Blahova, Miroslava; Zimmermann, Henning W.; Jitschin, Regina; Mougiakakos, Dimitrios; Mackensen, Andreas; Weston, Chris J.; et al. (Journal of Immunology, 2015)
Myeloid-derived suppressor cells (MDSC) represent a unique cell population with distinct immunosuppressive properties that have been demonstrated to shape the outcome of malignant diseases. Recently, human hepatic stellate cells (HSC) have been reported to induce monocytic-MDSC from mature CD14(+) monocytes in a contact-dependent manner. We now report a novel and unexpected mechanism by which CD14(+)HLADR(low/-) suppressive cells are induced by catalase-mediated depletion of hydrogen peroxide (H2O2). Incubation of CD14(+) monocytes with catalase led to a significant induction of functional MDSC compared with media alone, and H2O2 levels inversely correlated with MDSC frequency (r = -0.6555, p < 0.05). Catalase was detected in primary HSC and a stromal cell line, and addition of the competitive catalase inhibitor hydroxylamine resulted in a dose-dependent impairment of MDSC induction and concomitant increase of H2O2 levels. The NADPH-oxidase subunit gp91 was significantly increased in catalase-induced MDSC as determined by quantitative PCR outlining the importance of oxidative burst for the induction of MDSC. These findings represent a so far unrecognized link between immunosuppression by MDSC and metabolism. Moreover, this mechanism potentially explains how stromal cells can induce a favorable immunological microenvironment in the context of tissue oxidative stress such as occurs during cancer therapy.
EVALuna2:25703